2020
DOI: 10.1097/bot.0000000000001842
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory and Coagulative Considerations for the Management of Orthopaedic Trauma Patients With COVID-19: A Review of the Current Evidence and Our Surgical Experience

Abstract: Mounting evidence suggests that the pathogenesis of coronavirus disease 2019 (COVID-19) involves a hyperinflammatory response predisposing patients to thromboembolic disease and acute respiratory distress. In the setting of severe blunt trauma, damaged tissues induce a local and systemic inflammatory response through similar pathways to COVID-19. As such, patients with COVID-19 sustaining orthopaedic trauma injuries may have an amplified response to the traumatic insult because of their baseline hyperinflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“… 40 The hyperinflammatory and hypercoagulable state induced by COVID-19 infection may therefore amplify the initial inflammatory response to low-energy trauma such as a hip fracture (i.e., “first hit”), and thereby predispose this high risk patient population to a catastrophic “second hit”. 41 …”
Section: Discussionmentioning
confidence: 99%
“… 40 The hyperinflammatory and hypercoagulable state induced by COVID-19 infection may therefore amplify the initial inflammatory response to low-energy trauma such as a hip fracture (i.e., “first hit”), and thereby predispose this high risk patient population to a catastrophic “second hit”. 41 …”
Section: Discussionmentioning
confidence: 99%
“…Hence, determining the cut-off point for T cells, especially CD4+ and CD8+ T cells after the development of COVID-19 symptoms, can be a valuable prognostic indicator and may predict disease progression (158). However, in individuals with severe COVID-19, the frequencies of CD8+ T cells that express activation markers such as HLA-DR and exhaustion markers including PD-1, Tim-3, and NKG2A are higher than in mild cases (16,225,255). Thus, activated CD8+ T cells in patients with critical and severe COVID-19 have reduced degranulation and secretion of granzyme B (GrZB) and perforin as compared to healthy donors (225,243).…”
Section: Cd8+ T Cellmentioning
confidence: 99%
“…In the setting of trauma, although traumatic insult is considered as the first driver of inflammatory responses, other hyperinflammatory states, such as COVID-19, has also the capacity to augment the inflammation (16,17). Recent evidence reported elevated inflammatory response in COVID-19 patients sustaining orthopaedic trauma injuries due to their baseline hyperinflammatory states (16). Moreover, it has been documented that the clinical characteristics of COVID-19 patients with fractures were more serious than those of patients without fractures (18).…”
Section: Introductionmentioning
confidence: 99%
“…Patients who sustain hip fractures are often elderly with a high comorbidity burden, increasing risk of poor COVID-19 outcomes [5][6][7][8][9][10][11][12]. Overlapping inflammatory responses between orthopedic injury and SARS-CoV-2 infection may also contribute to poor outcomes [13][14][15]. Several studies have shown COVID-positive status in hip fracture patients to be associated with increased 30-day mortality [2,12].…”
Section: Introductionmentioning
confidence: 99%